The effect of using lean production techniques in improving product quality - an exploratory study in the General Organization for the Automotive Industry in Alexandria - محمود فهد عبد علي الدليمي; علي محمد عبد الكاظم (Iraqi Journal for Administrative Sciences, 2024)
This search Based on two variables are Lean production system and improve the quality of products target detection the relationship between lean production It is the adoption of tools(5S workplace organization, Just In Time ,kaizen , Kanaban ,Value stream Mapping ,Total productive Maintenance, Standardized work) and its Improve product quality in its dimensions(Performance, Reliability, Matching, Durability, Serviceability, Aesthetics, Perceived Quality) Selected sample State Company For Automotive Industry (Iskandariah),one of companies related to the Ministry of industry and Minerals, The problem came, Do I have researched the organization a clear vision for the slim dimensions of the system of production and quality of products? Is there a relationship between Lean production and dimensions of quality?, The research aims to knowing how for the sample company adopts concept of lean production in its tools in improve the quality of products ,therefore research recommended the company with group of recommendations, Benefit from the experiences of developed countries, especially Japan, which is the source of Lean production through modern ways that have been used to gain access to the Lean production and promote its goals.